2019
DOI: 10.26822/iejee.2019450789
|View full text |Cite
|
Sign up to set email alerts
|

The Inefficiency of Vocabulary Instruction

Abstract: Several researchers have advocated explicit instruction of vocabulary in order to help students improve their reading comprehension, especially low-achieving readers who need to "catch-up" to their age peers. Very few studies, however, have attempted to compare the time efficiency of direct instruction to its alternatives. In this review, I calculate the efficiency of vocabulary instruction in 14 studies taken from a recent research review (Wright & Cervetti, 2017). I then compare those results with estimates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The metanalysis by Wasik et al ( 2016 ) revealed that direct explicit vocabulary instruction proved to be more efficient in the learning of new words compared to incidental instruction of new vocabulary. However, this contrasts with other reviews that have taken into account the efficiency of instruction (number of words learned divided by instructional time), along with the feasibility and worth of providing direct vocabulary instruction, which revealed that simply listening to a story was more efficient for vocabulary acquisition than reading plus extended instruction (McQuillan, 2019a , 2019b ; see also Mason et al, 2008 ; Nagy et al, 1985 ). While our study was not designed to assert which of the two approaches is more effective in vocabulary instruction (see Wright & Cervetti, 2017 , for a recent review), what is clear from our experiment is that incidental learning of vocabulary may benefit from a (perceptual) contextual diversity manipulation in the classroom.…”
Section: Discussionmentioning
confidence: 70%
“…The metanalysis by Wasik et al ( 2016 ) revealed that direct explicit vocabulary instruction proved to be more efficient in the learning of new words compared to incidental instruction of new vocabulary. However, this contrasts with other reviews that have taken into account the efficiency of instruction (number of words learned divided by instructional time), along with the feasibility and worth of providing direct vocabulary instruction, which revealed that simply listening to a story was more efficient for vocabulary acquisition than reading plus extended instruction (McQuillan, 2019a , 2019b ; see also Mason et al, 2008 ; Nagy et al, 1985 ). While our study was not designed to assert which of the two approaches is more effective in vocabulary instruction (see Wright & Cervetti, 2017 , for a recent review), what is clear from our experiment is that incidental learning of vocabulary may benefit from a (perceptual) contextual diversity manipulation in the classroom.…”
Section: Discussionmentioning
confidence: 70%
“…Free reading provides another means of increasing vocabulary. In fact, there is evidence that free reading can be as or more efficient than explicit vocabulary instruction in building vocabulary, as well as being more enjoyable (Krashen, 2012; McQuillan, 2019b; McQuillan, 2020)—particularly when students are empowered to choose reading materials that interest them (e.g., Guthrie and Klauda, 2014; Miller, 2009). It is critical, however, that texts are well‐matched to a student’s instructional level.…”
Section: Discussionmentioning
confidence: 99%
“…The will to read influences the skill of reading and vice versa; a reciprocal relationship exists between intrinsic reading motivation and reading skill [54]. Children who frequently read fiction and are avid readers also benefit from an enriched vocabulary [37,55] and a wider knowledge of the world [10]. Additionally, several researchers highlight that the quality and degree of challenge offered by the reading materials, and the later discussion of the text, mediate the impact on reading comprehension and attainment, e.g., [56][57][58][59].…”
Section: Reading Children's Literature and Academic Benefitsmentioning
confidence: 99%